The Role of PAI Teachers in Embedding the Value of Wasathiyah Islam in Students of Al Madinah Islamic Primary School - Ayu Safitri; Mukh. Nursikin (Pusat Studi Penelitian dan Evaluasi Pembelajaran, 2024)
Teachers have an important responsibility to guide students in understanding and practicing moderate Islamic teachings. The author explores various strategies and methods used by teachers in the learning process, as well as their impact on the formation of student character. Apart from that, it also reviews the challenges faced by teachers in implementing the Wasatiyah approach amidst the complexity of the school environment and other factors. This research provides in-depth insight into how Islamic Religious Education teachers can effectively play their role in instilling Wasatiyah values at the primary education level.